Bioreducible poly(urethane amine)s for robust nucleic acid transfection in stem cells. (19th June 2019) - Ye, Ying; Jin, Rong; Hu, Xiaoxin; Zhuang, Juhua; Xia, Wei; Lin, Chao
Abstract : Bioreducible poly(urethane amine)s can be designed and optimized for highly efficient delivery in vitro of DNA or SiRNA into adult or embryonic stem cells with low cytotoxicity. Abstract : The search for cationic polymeric carriers enabling robust gene transfection against stem cells remains a challenge. Herein, linear bioreducible poly(urethane amine)s (denoted as SSPUAs) with repeated disulfide and protonable amino groups were prepared and used as non-viral vectors for in vitro gene transfection of different stem cells. The polyurethane copolymers (denoted as SSBT) with varied molar ratios of 1, 4-bis(3-aminopropyl)piperazine (BAP) and tris(2-aminoethyl) amine (TAA) moieties could lead to superb transfection activity against human adipose-derived stem cells (hADSCs) and human bone marrow stem cells (hBMSCs). Data indicated that under optimal transfection conditions, SSBT10 with a BAP/TAA molar ratio of 90/10 caused the transfection of ∼60% of green fluorescence protein-positive (GFP + ) hADSCs, and SSBT30 with the ratio of 70/30 resulted in the transfection of ∼40% of GFP + hBMSCs. Also, the SSBT30 and polyurethane with BAP residues (denoted as SSBAP) could mediate efficient gene transfer into bone marrow stem cells of experimental animals such as SD rats, beagle dogs and rhesus monkeys, with ∼40–70% of GFP + cells. Additionally, the SSBAP elicited robust transfection ability (∼60% of GFP + cells) against E14 mouse embryonic stem cells without compromising the expression of multipotent stemness-related markers of the cells. Importantly, the transfection efficiencies of these SSPUAs were higher as compared to those yielded by 25 kDa branched polyethylenimine and Lipofectamine 2000 reagents as positive controls. The SSBT30 was further practical to deliver siRNAs into hADSCs for BCL2L2 or TRIB2 gene silencing, causing superior gene silencing efficacy to Lipofectamine 2000. Besides their high gene transfection or silencing efficacy, these SSPUAs revealed low cytotoxicity against stem cells. This study highlights the SSPUA system as a distinct platform for robust nucleic acid delivery into stem cells.